Data Assets and Enterprise Total Factor Productivity - Liu, Feng (Pacific International Journal, 2024)
The progression of digital transformation has rendered the assetization of data an inevitable trend. This paper investigates the relationship between data assets and total factor productivity using a sample of A-share listed companies in Shanghai and Shenzhen. We find that data assets enhance firms’ total factor productivity via two primary mechanisms: augmenting human capital and fostering innovation within firms. Moreover, this effect is particularly pronounced in large-scale firms, state-owned enterprises (SOEs), as well as firms located in regions characterized by high levels of digitization and economic policy uncertainty. This paper contributes to the literature by enriching and expanding the understanding of the economic consequences of data assets on firms’ total factor productivity, while providing a policy rationale for further promoting data assetization as a catalyst for innovation and development.